Modification of titanium dioxide catalysts and evaluation of photocatalytic degradation of chlorophenols under visible light irradiation - Tolosa, Nolan C. (2012)
Recently, design for water and wastewater treatment contaminated with recalcitrant organic pollutant has been receiving enormous attention from environmental scientists and engineers. Photocatalytic oxidation is one of the most promising processes which treat organic substances (i.e. cholorophenols) using titanium dioxide (TiO₂) catalysts in the presence of light energy. The main purpose of this study is to investigate the behavior of modified titanium dioxide catalysts in decomposing chlorophenols by photocatalytic oxidation or photodegradation in aqueous solution under visible light. The preparation of modified TiO₂ catalysts is done using the sol-gel method. Characterization of catalyst?s particles size, phase composition, crystal structure, density, morphology, elemental analysis, point of zero charge (pzc), and specific surface area were performed using the X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Spectrometer (EDS), mapping, mass titration and Brunauer, Emmett and teller (BET), respectively. The photocatalytic activity of selected using 2-chlorophenol *2-CP), 4-chlorophenol (4-CP) and 2,4-dichlorophenol (2,4-DCP) as target chemical was also conducted. All of the synthesized TiO₂ catalysts analyzed by XRD were composed of pure anatase with tetragonal crystal structure and with nanocrystalline size ranging from 8.62-10.27 nm. The specific surface areas of the synthesized TiO₂ samples were 2-5 times larger than the commercial Degussa P-25. Analytical elemental analysis using SEM-EDS-mapping was used to identify the presence of elements and ions. Lineweaver-Burk expression was used in order to get the Langmuir-Hinshelwood rate (k) and Langmuir adsorption (K) constants. Increasing the initial concentration of chlorophenols resulted in the increase in their computed half-lives due to competing reaction of intermediates or by-products with the chlorophenols.
Dissertation (Ph.D. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Chlorophenols -- Degradation; Titanium dioxide